MOOD STRUCTURE TYPE OF THE CLAUSE ANALYSIS IN ENGLISH TEXT BOOKS OF SMA: A DISCOURSE STUDY BASED ON SYSTEMIC FUNCTIONAL LINGUISTIC THEORY - Fatimah Kesuma Astuti (Edukasi Lingua Sastra, 2018)
This study aims at analyzing mood structure type of the clause on recount and procedure text in English textbooks of SMA where it was analyzed based on the mood structure types of the clause. It was designed as a descriptive qualitative study and discourse analysis. Data were collected through documentation method. The technique in collecting the data is by determining the source to be investigated, determining the supporting resources, and seeking the recount and procedure text on the English textbook. The Data were analyzed using Mood structure analysis suggested by M.A.K Haliday. In analyzing the data, the activities did by deep reading, identifying, classifying, analyzing, and calculating the percentages. Based on the results of the data analysis, the findings of this research can be stated as follows: (1) There are some types of mood structure in the English textbooks of SMA at the tenth grade students which published by Pusat Perbukuan Departemen Pendidikan Nasional especially on recount text, they are indicative: declarative mood (99,41%), indicative: interrogative mood (0,59%), and imperative mood (0%). (2) The results of mood structure type on procedure text are indicative: declarative mood (25,62%), indicative: interrogative mood (0%), and imperative mood (74,38%). (3) The results in the textbook which published by Yudhistira especially on recount text are indicative: declarative mood (98,94%), indicative: interrogative mood (1,06%), and imperative mood (0%), and also on procedure text are indicative: declarative mood (25%), indicative: interrogative mood (0%), and imperative mood (75%).